Factors Influencing People’s Doubt to Conduct Covid-19 Vaccination: A Scoping Review - Etika Emaliyawati; Donny Nurhamsyah; Jihan Salimah Aribah; Lisdiawati Lisdiawati; Fauziyyah Ratih Asfari; Femi Luih Nurhasanah; Khairun Nisa Rahmawati; Intan Humaeroh; Iis Kania Nurasiah Jamil; Gina Nurul Azmi; Indah Permata Artamia; Lia Yulia Maulina; Herlina Silviana; Hanna Budhiyana; Gun Gun Gulbudin; Intan Rukmana (Padjadjaran Acute Care Nursing Journal, 2021)
The Covid-19 pandemic has been considered a global challenge for all countries around the world. The strategy that can be done to control Covid-19 is to develop an effective vaccine. The targets for the first wave of vaccines are health workers, public officials, and the elderly. For the second wave, the targets are vulnerable groups and the general public. The lack of acceptance of the Covid-19 vaccination in the community causes the vaccination program to be less than optimal. The purpose of this study is to determine the factors that influence people's doubts about the Covid-19 vaccine. The literature review method used is a scoping review. Researchers searched for the scientific articles in the Google Scholar, Pubmed, and Ebscohost databases. The keywords that researchers used consisting of 2 languages, in English keyword Covid-19 vaccine AND doubt OR hesitation AND factor OR reason OR cause. The year published was the last 5 years, and articles were selected using critical appraisal tools from The Joanna Briggs Institute (JBI). After screening according to inclusion criteria, 8 articles were found. The conclusion from the results of the journal analysis is that there are factors that influence people to refuse vaccines, including people with low education so they believe more in negative issues about vaccines, are not sure about the side effects of vaccines, are afraid of being injected, lack of information about vaccines, believe that no need vaccines to avoid Covid-19, and people who don't believe in Covid-19.